Optimal. Leaf size=24 \[ \log \left (\frac {6}{\log \left (\frac {1}{2 \left (-1-e^2\right ) x}+x\right )}\right ) \]
________________________________________________________________________________________
Rubi [F] time = 0.82, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {-1-2 x^2-2 e^2 x^2}{\left (-x+2 x^3+2 e^2 x^3\right ) \log \left (\frac {-1+2 x^2+2 e^2 x^2}{2 x+2 e^2 x}\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-1+\left (-2-2 e^2\right ) x^2}{\left (-x+2 x^3+2 e^2 x^3\right ) \log \left (\frac {-1+2 x^2+2 e^2 x^2}{2 x+2 e^2 x}\right )} \, dx\\ &=\int \frac {-1+\left (-2-2 e^2\right ) x^2}{\left (-x+\left (2+2 e^2\right ) x^3\right ) \log \left (\frac {-1+2 x^2+2 e^2 x^2}{2 x+2 e^2 x}\right )} \, dx\\ &=\int \frac {-1+\left (-2-2 e^2\right ) x^2}{x \left (-1+\left (2+2 e^2\right ) x^2\right ) \log \left (\frac {-1+2 x^2+2 e^2 x^2}{2 x+2 e^2 x}\right )} \, dx\\ &=\int \left (\frac {1}{x \log \left (x-\frac {1}{2 x+2 e^2 x}\right )}+\frac {4 \left (1+e^2\right ) x}{\left (1-2 \left (1+e^2\right ) x^2\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )}\right ) \, dx\\ &=\left (4 \left (1+e^2\right )\right ) \int \frac {x}{\left (1-2 \left (1+e^2\right ) x^2\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx+\int \frac {1}{x \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx\\ &=\left (4 \left (1+e^2\right )\right ) \int \left (\frac {1}{2 \sqrt {2 \left (1+e^2\right )} \left (1-\sqrt {2 \left (1+e^2\right )} x\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )}-\frac {1}{2 \sqrt {2 \left (1+e^2\right )} \left (1+\sqrt {2 \left (1+e^2\right )} x\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )}\right ) \, dx+\int \frac {1}{x \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx\\ &=\sqrt {2 \left (1+e^2\right )} \int \frac {1}{\left (1-\sqrt {2 \left (1+e^2\right )} x\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx-\sqrt {2 \left (1+e^2\right )} \int \frac {1}{\left (1+\sqrt {2 \left (1+e^2\right )} x\right ) \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx+\int \frac {1}{x \log \left (x-\frac {1}{2 x+2 e^2 x}\right )} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.12, size = 20, normalized size = 0.83 \begin {gather*} -\log \left (\log \left (x-\frac {1}{2 x+2 e^2 x}\right )\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.79, size = 28, normalized size = 1.17 \begin {gather*} -\log \left (\log \left (\frac {2 \, x^{2} e^{2} + 2 \, x^{2} - 1}{2 \, {\left (x e^{2} + x\right )}}\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.33, size = 28, normalized size = 1.17 \begin {gather*} -\log \left (\log \left (\frac {2 \, x^{2} e^{2} + 2 \, x^{2} - 1}{2 \, {\left (x e^{2} + x\right )}}\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.31, size = 31, normalized size = 1.29
method | result | size |
norman | \(-\ln \left (\ln \left (\frac {2 x^{2} {\mathrm e}^{2}+2 x^{2}-1}{2 \,{\mathrm e}^{2} x +2 x}\right )\right )\) | \(31\) |
risch | \(-\ln \left (\ln \left (\frac {2 x^{2} {\mathrm e}^{2}+2 x^{2}-1}{2 \,{\mathrm e}^{2} x +2 x}\right )\right )\) | \(31\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.53, size = 31, normalized size = 1.29 \begin {gather*} -\log \left (-\log \relax (2) + \log \left (2 \, x^{2} {\left (e^{2} + 1\right )} - 1\right ) - \log \relax (x) - \log \left (e^{2} + 1\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.52, size = 30, normalized size = 1.25 \begin {gather*} -\ln \left (\ln \left (\frac {2\,x^2\,{\mathrm {e}}^2+2\,x^2-1}{2\,x+2\,x\,{\mathrm {e}}^2}\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.29, size = 29, normalized size = 1.21 \begin {gather*} - \log {\left (\log {\left (\frac {2 x^{2} + 2 x^{2} e^{2} - 1}{2 x + 2 x e^{2}} \right )} \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________